Novel chromosomal translocation t(7;14)(q36.3;q11.2)dn in a female child with dysmorphic features - Jean-Pierre Antunes Gonçalves; Liliana Pinheiro; Maria João Magalhães; Arnaldo Cerqueira; Eduarda Abreu; Albina Silva; Carla Sá; Almerinda Pereira (Hygeia Press di Corridori Marinella, 2014)
When evaluating a newborn with peculiar phenotype it is mandatory to perform chromosomal studies. In this case report, the genetic study revealed a novel de novo translocation involving chromosome 7 and 14, thus establishing the following karyotype: as 45,XX,der (7)t(7;14)(q36.3;q11.2),-14dn.ish 7q36.3(VIJyRM2185 enh).mpla 7qsubtel(P036-E1,P070-B2)x3,14q11.2(P036-E1,P070-B2)x1.